2005
DOI: 10.1002/cncr.21598
|View full text |Cite
|
Sign up to set email alerts
|

Successes and failures of the teachable moment

Abstract: Objective We utilized the amyloid imaging ligand Pittsburgh Compound B (PiB) to determine the presence of Alzheimer's disease (AD) pathology in different mild cognitive impairment (MCI) subtypes and to relate increased PiB binding to other markers of early AD and longitudinal outcome. Methods Twenty‐six patients with MCI (13 single‐domain amnestic‐MCI [a‐MCI], 6 multidomain a‐MCI, and 7 nonamnestic MCI) underwent PiB imaging. Twenty‐three had clinical follow‐up (21.2 ± 16.0 [standard deviation] months) subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
294
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 325 publications
(304 citation statements)
references
References 120 publications
(166 reference statements)
4
294
0
5
Order By: Relevance
“…major surgery is a strong motivator; however other authors argue that teachable opportunities are often missed altogether, for example on diagnosis of cancer, stroke or peripheral vascular disease (Mukherjee et al, 2002;Gritz et al, 2005;Croquelois and Bogousslavsky, 2006). A major health benefit occurs whenever patients stop smoking so there is still value in stopping even after a serious smoking-related disease has been identified (Gritz et al, 2005). This supports the need for stop smoking services in acute hospitals and the importance of identifying all patients who are ready to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…major surgery is a strong motivator; however other authors argue that teachable opportunities are often missed altogether, for example on diagnosis of cancer, stroke or peripheral vascular disease (Mukherjee et al, 2002;Gritz et al, 2005;Croquelois and Bogousslavsky, 2006). A major health benefit occurs whenever patients stop smoking so there is still value in stopping even after a serious smoking-related disease has been identified (Gritz et al, 2005). This supports the need for stop smoking services in acute hospitals and the importance of identifying all patients who are ready to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this sense of stigma they were still smoking, so clinical staff need to be sensitive to the broader contexts in patients' lives that impact on their smoking behaviour and the stage of change a person has reached (Zimmerman et al, 2000;Graham, 2007). As Gritz et al (2005) explain for example, cancer patients may be psychologically vulnerable at this time and sensitive to any perceived blame for their condition. Indeed, this study found that a non-blaming, non-judgemental approach from the stop smoking staff was important if they wanted their message to be heard and accepted by smokers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations